Farmer strategies for tree crop diversification in the humid tropics. A review - Schroth, Götz; Ruf, François (Agronomy for sustainable development, 2014)
Many tree crop farms in the tropics are in a process of crop diversification, even in regions that have traditionally been dominated by a single tree crop species. Here, we review the factors that drive diversification and that influence farmer choices. We analyze recent literature from tropical Latin America, Africa, Asia, and the Pacific Islands, with emphasis on West and Central Africa. We use a framework that distinguishes farmer objectives in diversifying; the opportunities and constraints caused by environmental, technological, market, and policy factors; and farmer characteristics. Our main findings are: (1) Farmers diversify to increase their income by adding more lucrative crops. They diversify also to spread their income to lean times between the harvests of their traditional crops. In addition, farmers diversify to maintain or increase their food security especially while young tree crops are maturing and to reduce their vulnerability to environmental, market, and policy shocks. (2) Famers take advantage of opportunities and are subject to constraints. These include: heterogeneous site characteristics; the legacy of previous forest vegetation; emergent market opportunities from growing urban centers; a diversity of products and market outlets for some crops that reduces marketing risks; government policies; labor constraints that favor certain crops; the availability of investment capital that influences particularly the timing of diversification decisions; and access to improved planting material. (3) Diversification decisions also depend on farmer characteristics such as their age, education, financial situation, and farm and family size. Young farmers are not always more active in diversification than older farmers, although diversification and crop change are often related to generational change. Returning urban migrants have often had a positive effect in terms of diversification and innovation. (4) Diversification is often a response to structural environmental degradation caused by decades of tree crop monocultures. We conclude with a list of areas where government and non-government organizations can support farmers in their diversification decisions.